Sosialisasi Motivasi dan Literasi Pada Anak-anak Panti Asuhan Ananda Kota Palembang - Agung Anggoro Seto (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
This community service activity aims to provide motivation and literacy to children at the Ananda Orphanage, Palembang City. The activity method uses socialization techniques with several stages including situation analysis, communication, socialization and evaluation. The activity was carried out incidentally for 1 day with the number of participants involved as many as 40 children. The results of the activity show that the socialization of motivation and literacy activities for the children at the Ananda Orphanage has had a positive impact on the motivation of the children at the Ananda Orphanage in Palembang City, although there are still some deficiencies.